The Social Dilemma of Microinsurance: A Framed Field Experiment on Free-Riding and Coordination - Wendy Janssens; Berber Kramer (Tinbergen Institute, 2012)
Health shocks are among the most important unprotected risks for microfinance clients, but the take-up of micro health insurance typically remains limited. This pa- per attributes low enrollment rates to a social dilemma. Our theory is that in jointly liable groups, insurance is a public good. Clients can rely on contributions from group members to cope with shocks. Less risk averse clients have a private incentive to free-ride and forgo individual insurance even when insurance optimizes group welfare. The binding nature of insurance offered at the group level eliminates such free-riding. A framed public good experiment in Tanzania, eliciting demand for group versus individual microinsurance, yields substantial support for this hypothesis. This provides a potential explanation for low take-up rates.
Keywords: D71; I13; G21; 330; Health insurance; microfinance; risk-sharing; public goods experiment